The glucagon-like peptide 1 receptor agonist liraglutide attenuates placental ischemia-induced hypertension - Younes, Subhi Talal (Am J Physiol Heart Circ Physiol, 2020)
Preeclampsia is a hypertensive disorder of pregnancy characterized by systemic perturbations of nitric oxide function, reflective of generalized endothelial dysfunction. Therapies that target the nitric oxide pathway have shown promise in both clinical and preclinical studies of preeclampsia. The glucagon-like peptide 1 agonists have been shown to increase nitric oxide and lower blood pressure in patients with diabetes, in part, through activation of nitric oxide synthase (NOS). Therefore, we hypothesized that a direct acting glucagon-like peptide 1 receptor agonist would improve stigmata of the preeclampsia syndrome. Using the reduced uterine perfusion pressure rat model, we found that treatment with liraglutide significantly lowered blood pressure, improved renal function, and upregulated NOS3 protein expression in the mesenteric arterial bed. However, there were adverse effects on pup growth that were likely related to diminished food intake in the dams. Collectively, these data support the premise that the use of drugs that improve NOS abundance, including the glucagon-like peptide 1 agonists, is a rational therapeutic approach to the treatment of preeclampsia, but suggest cautious and careful study of their safety before potential clinical use in humans. NEW & NOTEWORTHY Drugs that target the glucagon-like peptide-1 pathway such as liraglutide are already used clinically, and it has been shown to promote endothelial nitric oxide synthase (NOS3) expression. We demonstrate that liraglutide, a glucagon-like peptide 1 receptor (GLP-1R) agonist, lowers blood pressure, improves renal function, and upregulates NOS3 in a rat model of placental ischemia. These data suggest that drugs that target the nitric oxide system, including GLP-1R agonists, are a potential therapeutic option for preeclampsia.